The activation dependent adhesion of macrophages to laminin involves cytoskeletal anchoring and phosphorylation of the alpha 6 beta 1 integrin (The Rockefeller University Press, 1990)
Macrophages require activation with either PMA (Mercurio, A. M., and L. M. Shaw. 1988. J. Cell Biol. 107:1873-1880) or interferon-gamma (Shaw, L. M., and A. M. Mercurio. 1989. J. Exp. Med. 169:303-308) to adhere to a laminin substratum. In the present study, we identified an integrin laminin receptor on macrophages and characterized cellular changes that occur in response to PMA activation that facilitate laminin adhesion. A monoclonal antibody (GoH3) that recognizes the integrin alpha 6 subunit (Sonnenberg, A., H. Janssen, F. Hogervorst, J. Calafat, and J. Hilgers. 1987. J. Biol. Chem. 262:10376-10383) specifically inhibited adhesion to laminin-coated surfaces. This antibody precipitated an alpha 6 beta 1 heterodimer (Mr 130/110 kD) from 125I surface-labeled macrophages. The amount of radiolabeled receptor on the cell surface did not increase after PMA activation. Thus, the induction of laminin adhesion cannot be attributed to de novo or increased surface expression of alpha 6 beta 1. By initially removing the Triton X-100-soluble fraction of macrophages and then disrupting the remaining cytoskeletal framework, we observed that 75% of the alpha 6 beta 1 heterodimer on the cell surface is anchored to the cytoskeleton in macrophages that had adhered to a laminin substratum in response to PMA. Significant cytoskeletal anchoring of this receptor was not observed in macrophages that had adhered to fibronectin or tissue culture plastic, nor was it seen in nonadherent cells. PMA also induced phosphorylation of the cytoplasmic domain of the alpha 6 subunit, but not the beta 1 subunit. Phosphorylated alpha 6 was localized to the cytoskeletal fraction only in macrophages plated on a laminin substratum. In summary, our results support a mechanism for the regulation of macrophage adhesion to laminin that involves specific and dynamic matrix integrin-cytoskeletal interactions that may be facilitated by integrin phosphorylation.